Funções executivas, inteligência e funcionalidade em crianças e adolescentes com transtorno do déficit de atenção e hiperatividade - Rodrigues, Ana Carolina Rost de Borba Galimberti (2021)
The evaluation of Executive Functions (EF) and intelligence corresponds to a large area within the current neuropsychological evaluation, especially with regard to childhood and adolescence. Attention Deficit Hyperactivity Disorder (ADHD) is the most prevalent neurodevelopmental disorder, estimated in 3.4% of children and adolescents. More and more studies have demonstrated how EF are impacted in children diagnosed with ADHD. Although there is a propensity to study EF in ADHD, with regard to intelligence, little is known. This occurs because intelligence is usually considered as a control variable for studies. In addition to intelligence, it is essential that responsible professionals be attentive to the autonomy, independence and adaptive behavior of the subjects in their different contexts. Looking carefully at this variable is a fundamental aspect to reduce false positives among possible diagnoses. Thus, this dissertation chose to develop two studies. The first study corresponds to the comparison of EF performance and school performance in children and adolescents with and without diagnosis of ADHD and with different levels of intelligence. The sample consisted of 114 participants, aged between 6 and 14 years and 11 months, and was divided into two groups. The groups were divided by clinical diagnosis (having ADHD or not), and by intelligence level (borderline intelligence, lower and middle mean). Then, a group comparison analysis (Two-Way Anova) was performed. The results showed that the clinical group presented worse performance in tasks of inhibition control, working memory for texts, cognitive flexibility, fluency and school performance. In the group by intelligence level, the sample with borderline intelligence presented worse results in work memory tasks, fluency and school performance, regardless of whether they had ADHD or not. The findings confirm the need to consider intelligence in neurodevelopmental disorders beyond a variable to be controlled, because it is observed that having the diagnosis of ADHD or having different levels of intelligence impactindependently of the patient's cognition. So, from the care one should take when evaluating intelligence, in parallel, the need for the evaluation of adaptive behavior is highlighted. Therefore, study two corresponds to the development of a Guide to Adaptive behavior Interview in Childhood and Adolescence (GEFA), as well as to present its content validity. The GEFA was developed in three stages: theoretical and practical development, application of the protocol in a pilot sample and analysis of judges. For content validity, cohen's Kappa agreement index (k) was used for the adaptive behavior construct as an all, and to analyze the validity of the items and examples of the GEFA, the content validity index (CVI) was used. The results confirm that the GEFA presents good content validity, both for the general construct, as for items and examples. Thus, the GEFA is considered a semistructured interview that provides the accurate clinical view of adaptive behavior for different neurodevelopmental disorders. Understanding about EF, intelligence and adaptive behavior is a way to a more complete and practical neuropsychological evaluation, in which it provides space to reduce possible false positive diagnoses, besides enabling the development of different intervention strategies.